PENGARUH PENGARUH PENERAPAN MEDIA PEMBELAJARAN ADOBE ANIMATE CC TERHADAP HASIL BELAJAR GEOGRAFI SISWA KELAS X DI SMA NEGERI 7 PADANG - Priti Melini; Nofrion Nofrion (DEPARTEMEN GEOGRAFI FIS UNP, 2023)
Abstract The purpose of this study was to determine student geography learning outcomes between the control class and the experimental class and the effect of the application of Adobe Animate CC media on the geography learning outcomes of class X at SMA Negeri 7 Padang. This research used a quasi-experimental method with a quantitative approach. Population of this research is class X SMA Negeri 7 Padang, totaling 287 students. Sample in this research used a purposive sampling technique which divided into a control class, that is class X2 and an experimental class, that is class X3 with total of 36 students in each class. The research design used is Posttest Only Control Group Design. Data collection techniques through observation, tests, questionnaires, and documentation. Data analysis on the hypothesis test used a technique of independent sample t-test (t-test). The results of this research indicate that there is a significant difference in student learning outcomes between the control class using conventional learning media and the experimental class using Adobe Animate CC learning media. Besides that, based on the results of questionnaire data analysis regarding student responses, Adobe Animate CC learning media has a positive influence on learning activities. Keywords—Learning Media, Adobe Animate CC, Learning Outcomes, Geography Learning